Assessing flood exposure in informal districts: a case study of Bujumbura, Burundi. Issue 3 (3rd July 2019) - Kubwarugira, Gamaliel; Mayoussi, Mohamed; El Khalki, Yahia
Abstract : In most sub-Saharan African cities, urban growth is generally unplanned. Recent research studies analysed the vulnerability of these settlements to natural hazards and drew out challenges related to lack of integrated actions from stakeholders, inefficiency in housing structures and vulnerability of poorer households. But, we still need to document implications of urban growth management relying on status quo and regularization, in terms of worsening exposure to flooding. Filling the gap, this paper focuses on exposure to flooding of informal districts of Bujumbura City, Burundi. Results show that the zones where the town is expanding are the most exposed. Our aim is to alert inhabitants and urban planners, so that a proactive approach could be adopted. This is deemed to insure that specificities of every urban site are considered during an integrated urban planning, including flood mitigation in exposed sites in Bujumbura, and also in other cities facing the same issue of uncontrolled urbanization.